2007
DOI: 10.1002/jsfa.2815
|View full text |Cite
|
Sign up to set email alerts
|

Use of ozone in a lettuce‐washing process: an industrial trial

Abstract: Bacteria such as Escherichia coli and Salmonella spp. may cause serious problems for the quality maintenance of pre-packaged lettuces. The aim of this study was to evaluate the bactericidal effect of ozonated water in the washing of iceberg lettuce. For this purpose an ozone generator was integrated into a commercial lettuce-washing facility. Lettuce samples were removed from this process and analysed for mesophilic total viable count (TVC), E. coli, Salmonella spp., vitamin C and sugar content. The analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…However, once the vegetable was mixed with ozone OMBW, it easily lost its bactericidal activity, which was similar to the ordinary OW (Table 5). According to the evaluation experiments performed in a commercial lettuce washing facility, removing attached organic material from the leaves of vegetables by pre-washing was very important to prevent the reduction of dissolved ozone (Hassenberg et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…However, once the vegetable was mixed with ozone OMBW, it easily lost its bactericidal activity, which was similar to the ordinary OW (Table 5). According to the evaluation experiments performed in a commercial lettuce washing facility, removing attached organic material from the leaves of vegetables by pre-washing was very important to prevent the reduction of dissolved ozone (Hassenberg et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Cantaloupes may be especially difficult to disinfect, even if fully immersed in the sanitizing solution, because of microbial attachment within inaccessible sites in the netting and stem scar . Hassenberg et al (2007) reported only a small decrease in the population of microorganisms in lettuce washed with ozonated water in a commercial lettuce-washing facility.…”
Section: Efficacy Of Commercial Washersmentioning
confidence: 97%
“…Ozone surface treatment of fruit was reported to have minor effects on anthocyanin contents in strawberries [15] and blackberries [16] . There are numerous studies in the literature about the effect of ozone treatment on the safety and quality of iceberg lettuce, orange Juice, fresh cut green lettuce [17][18], Salmon -trout [19] and blackberry juice [20]. The use of ozone as a surface disinfectant of meats [21] and for the preservation of shrimps [22], broccoli sprouts [23] and Chicken [24] has been reported.…”
Section: Introductionmentioning
confidence: 99%